Wireless Sensor and Actor in Underwater Communication - Ashish, Abhijeet; Kumar, Pankaj (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
This paper represents the wireless communication system in underwater and also as well as underground system .the wireless sensor and actor work for this. The main motive for this paper is to gives the world a real communication to find any systems, obstacles, the wireless sensor sense the function which is happened in the water, and also helpful in underground. Wireless sensor & actor works on distributing sensing and acting task. The sensor collect the information from the real world and the actor perform the task to solve the communication process .this paper is very useful in the communication system in underwater.